Laser Additively Manufactured Iron-Based Biocomposite: Microstructure, Degradation, and In Vitro Cell Behavior - Yang, Youwen; Cai, Guoqing; Yang, Mingli; Wang, Dongsheng; Peng, Shuping; Liu, Zhigang; Shuai, Cijun (Frontiers in Bioengineering and Biotechnology, 2021)
Too slow degradation of iron (Fe) limits its orthopaedics application. In this study, calcium chloride (CaCl2) was incorporated into Fe based biocomposite fabricated by laser additive manufacturing, with an aim to accelerate the degradation. It was found that CaCl2 with strong water absorptivity improved the hydrophilicity of Fe matrix, and thereby promoted the invasion of corrosive solution. On the other hand, CaCl2 could rapidly dissolve once contacting solution and release massive chloride ion. Interestingly, the local high concentration of chloride ion effectively destroyed the corrosion product layer due to its strong erosion ability. As a result, the corrosion product layer covered on Fe/CaCl2 matrix exhibited an extremely porous structure, thus exhibiting a significantly reduced corrosion resistance. Besides, in vivo cell testing proved that Fe/CaCl2 biocomposite also showed favorable cytocompatibility.